Verslo informacijos kokybės vertinimas - Ruþevičius, Juozas; Gedminaitė, Aistė (Information & Media, 2007)
Straipsnyje analizuojami verslo informacijos kokybës vertinimo ypatumai. Iðryðkinami svarbiausi informacijos kokybës rodikliai – informacijos kokybës vertinimo ir valdymo pagrindas. Remiantis IBM kompanijos modeliu ávertinama Lietuvos verslo organizacijø informacinë branda. Identifikuojami mûsø ðalies verslo organizacijø labiausiai vertinami informacijos kokybës rodikliai. Daroma iðvada, kad siekiant uþtikrinti kokybæ informacija turëtø bûti kuriama, pateikiama ir vertinama pagal konkreèiai apibrëþtus kokybës kriterijus, kaip pagal ið anksto aptartus kokybës kriterijus yra tiekiami ir vertinami kiti produktai – prekës ar paslaugos. Konkreèiai vartotojø grupei svarbiausiø informacijos kokybës charakteristikø identifikavimas, jø matavimo ir vertinimo kriterijø, metodologijos nustatymas yra verslo informacijos objektyvesnio kokybës ávertinimo pagrindas.Business information quality assessmentJuozas Ruþevièius, Aistë GedminaitëSummaryThe objective of the article is to highlight the key information quality dimensions, define its management, assessment peculiarities and according to the results of the questionnaire research to assess Lithuanian business organizations’ information maturity level and also distinguish the prime information quality indicators for them. The organizations’ information maturity was assessed according to a model proposed by IBM Corporation. This model describes five stages of maturity of information use and estimates how organizations realize, value and use information to drive business development and competitiveness (Stage I – data to run the business; II – information to manage the business; III – information as a strategic asset; IV – information to enable innovation; V – information as a competitive differentiator).An information consumer research has shown that only one third of the respondents work in companies that on the highest information maturity level. Almost 11 percent of the respondents have noted that information for their companies means to enable innovations. This fourth level just slightly differs from the fifth level where information becomes a competitive advantage. Consequently, these fourth level organizations progress to the right trend. However, more than a half of the surveyed organizations are on lower information maturity levels. To conclude, Lithuanian organizations still do not use all information potentiality to gain business development and increase competitiveness.The research findings show that the most important information quality dimension for Lithuanian business organizations is information reliability. Nearly 80 percent of respondents indicated that reliability is an essential dimension. The information dimensions like relevance and accuracy are evenly important to information consumers: more than 60 percent of respondents pointed them as important. Surprisingly, from the list with 31 dimensions no one picked out the ease of information maintenance. To ensure information quality, information must be produced in accordance with clearly defined information quality dimensions, just like other products (services and goods) are supplied and evaluated according to specific quality characteristics."font-family: TimesLT; line-height: 18px;">